How Ironman triathletes balance oxidative stress - Neubauer, O.; Kern, N.; Nics, L.; Wagner, K. H. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Although regular physical training harvests a lot of beneficial physiological effects, some data implicate that there are also potentially harmful effects as a result of extreme exercise such as in ultra-endurance sports. However, our current understanding provides only scattered information e.g. whether the exercise-induced formation of free radicals can result in sustained oxidative damage and thus accumulative adverse responses. To address this issue in the most comprehensive manner, the possible health risks of an Ironman (IM) triathlon were explored specifically regarding oxidative, muscular/cardiac and inflammatory/ systemic stress. Materials and methods: The study comprised 48 nonprofessional well-trained male triathletes (mean±SD: age: 35.3±7 years, height 180.6±0.1cm, weight: 75.1±6.4kg, VO2 peak: 57,2±7.4ml kg-1 min-1) who participated in the 2006 IM Austria (3.8km swim, 180km cycle, 42.2km run). Plasma samples were taken 2 days before the race, within 20 min, 20-24 h, 5 days and 19 days after the race; 42 athletes completed the study. Up to date, plasma concentrations of malondialdehyde (MDA), conjugated dienes (CD) (both via HPLC) and oxidised low-density lipoprotein (ox- LDL) (with ELISA technique) have been assessed to specify the amplitude of oxidative stress (OS). In order to determine exercise-induced changes of antioxidant (AO) status and AO capacity, plasma concentrations of alpha- and gamma-tocopherol, carotenoids and ubichinone-50 were detected with HPLC. Plasma vitamin C and total radical trapping AO capacity (TRAP) were analysed photometrically. Results: Of the OS markers examined so far, only CD was significantly elevated immediately postrace compared with baseline (p<0.001), but levels returned to pre-exercise values within 24 h. Although MDA tended to rise directly after the race (p=0.077), there were no statistically significant changes during the monitoring period. Ox-LDL decreased significantly below pre-exercise values immediately postrace (p<0.05) and declined further on the day after the IM (p<0.001). 5 days after it had returned to baseline. Ox- LDL:LDL ratio was not significantly elevated one day after exercise (p=0.105). TRAP increased significantly in the course of the IM (p<0.001) and correlated positively with VO2 peak (r=0.304, p<0.05). The significant increases found in vitamin C (p<0.001) and alpha-tocopherol levels (p<0.001) immediately post-exercise compared to prerace values can be attributed to the intake of these AO during the race as well as to tissue mobilisation. Without corrections for changes in plasma volume, one day after race the concentrations of all plasma AO dropped below baseline significantly(probably reflecting increased AO consumption), except for vitamin C, which did not drop significantly. However, 5 days postrace most AO concentrations were similar to prerace values. Conclusion: To this point of the study, data indicate that there is no persistent OS in response to an IM triathlon probably due to training-induced adaptations in the AO defence system.